Indocyanine green utility in sentinel node detection for cervical cancer patients - Nicolae Bacalbașa; Irina Balescu; Cristian Balalau; Mihaela Vilcu; Iulian Brezean (Journal of Mind and Medical Sciences)
With wide implementation of screening tests for the Human Papilloma Virus, the number of diagnosed cases of premalignant or early stages of cervical cancer has increased considerably. As a consequence, surgeons’ attention has focused on determining how best to limit the surgical procedure so the benefits of the procedure will not be surpassed by postoperative morbidity. In this respect, extended lymph node dissection, routinely associated so far with cervical cancer patients, has in the last decades been replaced with sentinel node detection and biopsy. Initially performed through radiocolloid injection, this method has undergone permanent changes in order to maximize its efficacy and safety. Although the laparoscopic approach had been widely used in the past, a new method has been proposed, i.e., the use of indocyanine green injection, which has yielded promising results for sentinel node detection in the early stages of cervical carcinoma. This paper reviews the literature of the most relevant studies conducted on this topic.